1991
DOI: 10.1002/iroh.19910760410
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic Picoplankton: Community Composition, Abundance and Distribution across a Gradient of Oligotrophic British Columbia and Yukon Territory Lakes

Abstract: Autotrophic picoplankton communities were examined in eleven oligotrophic lakes from a broad geographic region of western Canada, representing a variety of physico-chemical and biological conditions. During our study, several of the lakes were treated with additions of inorganic nitrogen and phosphorus fertilizers. Picoplankton communities in most lakes were dominated (> 70 %) by unicellular or colonial coccoid cyanobacteria, provisionally identified by morphological and autofluorescence properties as Synechoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 36 publications
3
68
3
Order By: Relevance
“…As reported by Kraska et al (2006), the characteristic feature of the pelagic zone of the lake was the acid reaction of water (pH 5.6 in the epilimnion), which confirms reports (e.g. Stockner and Shortreed 1991) about the elimination of picocyanophytes resulting from decreasing water pH. The picophytoplankton of the other lakes were dominated by cyanophytes.…”
Section: Discussionsupporting
confidence: 87%
“…As reported by Kraska et al (2006), the characteristic feature of the pelagic zone of the lake was the acid reaction of water (pH 5.6 in the epilimnion), which confirms reports (e.g. Stockner and Shortreed 1991) about the elimination of picocyanophytes resulting from decreasing water pH. The picophytoplankton of the other lakes were dominated by cyanophytes.…”
Section: Discussionsupporting
confidence: 87%
“…It has recently been stated by Stockner et al (2000) that the abundance of microcolonies in many lakes is higher at the base of the euphotic zone than in surface waters (Stockner & Shortreed 1991, SimeNgando 1995. Schallenberg & Burns (2001), who reported highly significant positive correlations between the abundance of aggregated picocyanobacteria in Lake Wakatipu and concentrations of total phosphorus and total nitrogen, suggested that colonial picocyanobacteria respond positively to small increases in total nutrient concentrations and that colonial picocyanobacteria may contribute significantly to nitrogen fixation within the pelagial.…”
Section: Population Dynamics Of Colonial Picocyanobacteriamentioning
confidence: 98%
“…Most of these waters are oligotrophic (Smith et al 1984, Stockner & Shortreed 1991, Milot-Roy & Vincent 1994 in which the plankton community is likely to be strongly nutrient-limited and dominated by microbial food web components. Ultraviolet radiation (UVR) penetrates deep into oligotrophic, low DOC (dissolved organic carbon) waters (Morris et al 1995), and microbial responses to changes in phosphorus supply in these lakes (e.g.…”
Section: Introductionmentioning
confidence: 99%